Determinants of maternal sex steroids during the first half of pregnancy - Toriola, Adetunji T.; Vääräsmäki, Marja; Lehtinen, Matti; Zeleniuch-Jacquotte, Anne; Lundin, Eva; Rodgers, Kenneth-Gary; Lakso, Hans-Ake; Chen, Tianhui; Schöck, Helena; Hallmans, Goran; Pukkala, Eero; Toniolo, Paolo; et al. (Obstetrics & gynecology, 2011)
OBJECTIVE: - To examine the associations of maternal and child characteristics with early pregnancy maternal concentrations of testosterone, androstenedione, progesterone, 17-hydroxyprogesterone, and estradiol (E2). - METHODS: - We analyzed these hormones among 1,343 women with singleton pregnancies who donated serum samples to the Finnish Maternity Cohort from 1986 to 2006 during the first half of pregnancy (median 11 weeks). The associations of maternal and child characteristics with hormone concentrations were investigated by correlation and multivariable regression. - RESULTS: - Women older than age 30 years had lower androgen and E2 but higher progesterone concentrations than women younger than that age. Multiparous women had 14% lower testosterone, 11% lower androstenedione and 17-hydroxyprogesterone, 9% lower progesterone, and 16% lower E2 concentrations compared with nulliparous women (all P<.05). Smoking mothers had 11%, 18%, and 8% higher testosterone, androstenedione, and 17-hydroxyprogesterone levels, respectively, but 10% lower progesterone compared with nonsmoking women (all P<.05). E2 concentrations were 9% higher (P<.05) among women with a female fetus compared with those with a male fetus. - CONCLUSION: - Parity, smoking, and, to a lesser extent, maternal age and child sex are associated with sex steroid levels during the first half of a singleton pregnancy. The effects of smoking on the maternal hormonal environment and the possible long-term deleterious consequences on the fetus deserve further evaluation. - LEVEL OF EVIDENCE: - II
Gesehen am 16.11.2022